Reading for Water. Issue 3 (3rd April 2022) - Hofmeyr, Isabel; Nuttall, Sarah; Lavery, Charne
Abstract : This introduction provides a wide-ranging framing for a set of essays that explores the topic "Reading for Water" in southern African literature. The introduction begins by demonstrating this method through snapshots of three seminal South African novels: Marlene van Niekerk's Agaat (2006), A. C. Jordan's The Wrath of the Ancestors (1980) and J. M. Coetzee's Life & Times of Michael K (1983). This is followed by a discussion of Sarah Nuttall's essay on Namwali Serpell's The Old Drift, which establishes the framework for the essays that follow. These are discussed under four sections: Hydro-infrastructures, Multi-spirited Water, Bodies of Water and Wet Ontologies, and New Genealogies, New Chronotopes.